Penerapan Metode Complex Proportional Assessment (Copras) Dalam Pemilihan Mahasiswa Terbaik di Kelas 4-3 - Annisa Syaharani; Annisa Putri; Rostika Tnunay; Yuyun Dwi Lestari (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
This research aims to apply the COPRAS (Complex Proportional Assessment of Alternatives with Ranking) method in selecting the best students in class 4-3 at Harapan University, Medan. The COPRAS method is used to integrate various assessment criteria, such as GPA, attendance, attitude, activeness and discipline, to produce an objective and transparent evaluation. The research results show that the application of this method succeeded in providing an effective solution in determining the best students. Based on the analysis results, Rili Aditya obtained the highest score with a utility value of 100%, so he was declared the best student among the other candidates. The COPRAS method not only increases assessment accuracy, but also encourages the creation of healthy competition among students. By implementing a decision support system based on the COPRAS method, educational institutions can evaluate student performance more consistently and effectively